INSIGHTS INTO THE ECOPHYLOGEOGRAPHY OF CASSAVA MOSAIC DISEASE VIRUSES IN YANGAMBI, DRC - Tshilenge, Jean-Claude Lusenge; Bolumbu, Marie-Louise Mbuya; Grasser, Klaus-Dieter; Marie, Sophie Leclercq (Contemporary Journal of Advancement in Food Science and Technology (CJAFST), 2023)
Cassava mosaic disease (CMD) poses a significant threat to cassava cultivation in Africa, with devastating consequences for the agricultural sector. It is widely recognized as a primary concern in the region due to its destructive impact on cassava crops. The prevalence of dual infections involving African cassava mosaic virus (ACMV) and East African cassava mosaic virus-Uganda (EACMV-UG) is particularly associated with the extensive spread of CMD across the continent. This phenomenon has been well-documented in various studies, highlighting the critical role of these viruses in CMD proliferation. Notably, CMD's expansion has been traced from its epicenter in Uganda to neighboring countries, including the Democratic Republic of Congo (DRCongo).